The nursing care to the child submitted to the chemotherapy - Avanci, Barbara Soares (2010)
Objective: to identify the main difficulties of the child submitted to the chemotherapy and discuss the nursing care to the child submitted to the chemotherapy. Methodos: a exploratory, qualitative, bibliographical study, accomplished at the Virtual Health Library (LILACS and BDENF), where was accomplished a pre-reading and selective reading, selecting 10 scientific productions, which was accomplished the interpretative reading and thematic analysis. Results: like this, was resulted in the following categories: the main difficulties of the child submitted to the chemotherapy, and the importance of the nursing care to the child submitted to the chemotherapy. Conclusion: the child underwent chemotherapy and his family need a continuous support, it is not easy to live or even monitor the entire process. It is important that the family and children are always well informed to minimize your anxieties and doubts, therefore, it’s ended that the nurse is an important mediator for the promotion of the health of the child submitted to the chemotherapy.